Ecosystem-level carbon stocks and sequestration rates in mangroves in the Cananeia-Iguape lagoon estuarine system, southeastern Brazil - Rovai, Andre S.; Coelho-Jr, Clemente; Almeida, Renato de; Cunha-Lignon, Marilia [UNESP]; Menghini, Ricardo P.; Twilley, Robert R.; Cintron-Molero, Gilberto; Schaeffer-Novelli, Yara (Elsevier B.V., 2021)
Mangroves fringe the coastlines of 54% of the world's nations but convey ecosystem services, such as carbon sequestration, that span administrative boundaries. Despite their high carbon sequestration efficiency and longterm storage capacity, few countries have assembled detailed mangrove carbon inventories. For example, Brazil, which detains the second largest mangrove area in the world, still lacks a detailed inventory on its blue carbon resources, largely due to the scarcity of integrated ecosystem-level (that is, carbon stored in biomass and soil combined) carbon assessments. Here we combine published and unpublished data to derive an inventory on ecosystem-level carbon stocks and carbon sequestration rates in the Cananeia-Iguape lagoon estuarine system, southeastern Brazil. We find that mangroves in the study area have the largest per-unit-area ecosystem-level carbon stocks at 380 MgC ha(-1) when compared to other Brazilian mangroves. Soil organic carbon stocks (top meter) account for 70% of this total. Annual carbon sequestration in mangrove soils and woody biomass combined with carbon fluxes via litterfall total 0.16 TgC yr(-1). Degradation of mangrove ecosystems in this region could lead to CO(2)e emissions up to 1,395 MgCO2 ha(-1) and reduce annual carbon sequestration in soil and biomass combined, and carbon flux via litterfall by 27 and 12 MgCO2 ha(-1) yr(-1), respectively. Our results provide coastal wetlands managers and scientists with novel information on mangrove carbon stocks and sequestration rates in the study area, which is useful to strengthen regional blue carbon and potential CO(2)e emission inventories. These estimates can also be used to establish performance measures to inform restoration targets as well as to serve as a baseline for comparison with current and future measurements of carbon stocks and fluxes in response to environmental change.
Keywords: Biomass; Net primary productivity; Blue carbon; Carbon accretion; Carbon burial; Carbon fluxes